Activation and regulation of primary metabolism during seed germination. Issue 1 (17th February 2014) - Rosental, Leah; Nonogaki, Hiroyuki; Fait, Aaron
Abstract: Seed germination is regulated in a concerted manner that involves generating growth potential in the embryo to overcome the mechanical resistance of the endosperm. The wake-up call of a dry seed includes the reorganization of subcellular structures and the reactivation of metabolism in a dense, oxygen-poor environment. Pools of unbound metabolites and solutes produced by the degradation of storage reserves, including starch, proteins and oils, in the embryo can contribute to the generation of the embryo growth potential and radicle protrusion. Recent genomics studies have contributed a vast amount of data on protein, metabolite and gene transcript profiles during germination, which can be integrated to explore the seed metabolism from water imbibition to radicle protrusion. To what extent are free pools of metabolites relevant to the reorganization of seed metabolism? How is energy built to support embryo growth and radicle protrusion? Elucidating these fundamental questions in seed biology is the key to the understanding of the germination process. Here we have attempted to summarize the recent scientific knowledge to provide a comprehensive description of the ignition, reassembling and regulation of metabolism during seed germination.